Terapi Psikoedukasi terhadap Self Care Activity pada Penderita Diabetes Mellitus - Argi Virgona Bangun; Fitria Ningsih (Journal of Telenursing (JOTING), 2021)
This study aims to determine the difference in the mean before and after the implementation of psychoeducation therapy on self-care activities in diabetes mellitus sufferers in RW 07 in the work area of Puskesmas Cimahi Tengah. The method in this study used a pre-experiment, with a one group pretest-posttest research design. The sample in this study were patients with type 2 diabetes millitus. This study used a consecutive sampling of 11 respondents. Psychoeducation therapy was given for 5 meetings in 21 days and measurement of self-care activity using the SDSCA questionnaire, then the data were processed using univariate analysis (mean, SD, 95% CI, and Min-Max) and bivariate (t-dependent test). The pretest results obtained were 10.63 and the posttest was 23.00 and the Pvalue was 0.001. In conclusion, there is an effect of psychoeducation therapy on self-care activity in diabetes mellitus sufferers. Keywords: Diabetes Millitus, Psychoeducation, Self-Care Activity